Psychological Determinants of Teacher-Student Relationships in Primary Class - Mirkosimova H. M. (Euro Asian Journal Publishing, 2023)
Based on a systematic approach, the activity, institutional and personal aspects of the teaching profession are considered, which made it possible to determine the factors that determine the very essence of the teaching profession. A typology of teacher personality is proposed, built on the basis of various characteristics of the system. Such characteristics of the teaching profession as artificiality, controllability, complexity, activity, instability, and stochasticity are substantiated. The following patterns of functioning of the teaching profession are proposed and characterized: integrity, communication, hierarchy, equifinality, necessary diversity, historicity, synergy. The conclusion is made about the need to consider the teaching profession not only as a result or process, but also as a social institution.
Keywords: teaching profession; system; typology of teacher personality